2020
DOI: 10.33029/0206-4952-2020-41-2-135-143
|View full text |Cite
|
Sign up to set email alerts
|

A heterologous virus-vectored vaccine for prevention of Middle East respiratory syndrome induces long protective immune response against MERS-CoV

Abstract: Федеральное государственное бюджетное учреждение «Национальный исследовательский центр эпидемиологии и микробиологии имени почетного академика Н.Ф. Гамалеи» Министерства здравоохранения Российской Федерации, 123098, г. Москва, Российская Федерация 2 Федеральное автономное образовательное учреждение высшего образования Первый Московский государственный медицинский университет имени И.М. Сеченова Министерства здравоохранения Российской Федерации (Сеченовский Университет), 119991, г. Москва, Российская Федерация … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 2 publications
0
8
0
3
Order By: Relevance
“…The sample size for both studies was calculated from previous clinical trials of a MERS vaccine 27 based on the same recombinant viral vectors as used in our vaccine but carrying the MERS-CoV glycoprotein S gene. Preliminary results of a study of a MERS vaccine in which more than 100 people participated showed a seroconversion rate of 100%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size for both studies was calculated from previous clinical trials of a MERS vaccine 27 based on the same recombinant viral vectors as used in our vaccine but carrying the MERS-CoV glycoprotein S gene. Preliminary results of a study of a MERS vaccine in which more than 100 people participated showed a seroconversion rate of 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results of a study of a MERS vaccine in which more than 100 people participated showed a seroconversion rate of 100%. 27 When calculating the sample size for our study, we expected 99% efficiency, which required inclusion of 16 participants in each study. Considering the possibility of early dropout of volunteers, we decided that 20 volun teers should be recruited into the immunogenicity assessment group in phase 2 of each study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although adenoviral vectors might induce immune responses against vector components and attenuate antigen-induced responses, prime-boost heterologous vaccination with two different vectors allows minimisation of this effect. 9 , 10 , 11 Thus, the most effective approach for generating a powerful and long-lasting immune response that does not depend on the presence of a pre-existing immune response to the vector is the heterologous prime-boost vaccination approach. We used this approach when developing a vaccine for the prevention of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The encouraging results of S-Trimer booster doses in this study also warrant the further evaluation of heterologous prime-boost strategies across different platforms, utilizing our protein-based S-Trimers a booster dose following primary vaccination series with adenovirus-vectored, mRNA, or inactivated COVID-19 vaccines. Some concerns have emerged around the safety of multiple doses of mRNA vaccines including potential polyethylene glycol (PEG) sensitization ( 28 ), and anti-vector immunogenicity for adenovirus-vectored vaccines are known to reduce the effectiveness of subsequent homologous doses ( 29,30,31 ). Preliminary human clinical data indicates that heterologous prime-boost with adenovirus-vectored and mRNA COVID-19 vaccines (or vice versa) suggest that they induce higher rates of systemic reactogenicity than heir homologous prime-boost counterparts ( 32 ), further warranting the evaluation of protein-based candidates as booster doses.…”
Section: Discussionmentioning
confidence: 99%